A margin-of-the-day online adaptive intensity-modulated radiotherapy strategy for cervical cancer provides superior treatment accuracy compared to clinically recommended margins: A dosimetric evaluation. (October 2013) - Ahmad, Rozilawati; Bondar, Luiza; Voet, Peter; Mens, Jan-Willem; Quint, Sandra; Dhawtal, Glenn; Heijmen, Ben; Hoogeman, Mischa
Abstract Purpose. To dosimetrically evaluate a margin-of-the-day (MoD) online adaptive intensity-modulated radiotherapy (IMRT) strategy for cervical cancer patients. The strategy is based on a single planning computed tomography (CT) scan and a pretreatment constructed IMRT plan library with incremental clinical target volumes (CTV)-to-planning target volumes (PTV) margins. Material and methods. For 14 patients, 9–10 variable bladder filling CT scans acquired at pretreatment and after 40 Gy were available. Bladder volume variability during the treatment course was recorded by twice-weekly US bladder-volume measurements. A MoD strategy that selects the best IMRT plan of the day from a library of plans with incremental margins in steps of 5 mm was compared with a clinically recommended population-based margin (15 mm). To compare the strategies, for each fraction that had a recorded US bladder-volume measurement, the CT scan with the nearest bladder volume was selected from the pretreatment CT series and from the CT series acquired after 40 Gy. A frequency-weighted average of the dose-volume histograms (DVH) parameters calculated for the two selected CT scans was used to estimate the DVH parameters of the fraction of interest. Results. The 15-mm recommended margin resulted in cervix-uterus underdosage in six of 14 patients. Compared with the 15-mm margin, the MoD strategy resulted in significantly better cervix-uterus coverage (p = 0.008) without a significant difference in the sparing of rectum, bladder, and small bowel. For each patient, 3–8 (median 5) plans were needed in the library of plans for the MoD strategy. The required range of the MoD was 5–45 mm (median 15 mm). Twenty-five percent of all fractions could be treated with a MoD of 5 mm and 81% of all fractions could be treated with a MoD up to 25 mm. Conclusions. Compared with a clinically recommended margin, a simple online adaptive strategy resulted in better cervix-uterus coverage without compromising organs at risk sparing.